The Ability of Course Students and Non Course Students at SMPN 19 Moncongloe in Reading Comprehension - Sitti Halijah; Ratnawati Ratnawati; Ratnasari Ratnasari (Tamaddun Life, 2016)
This study aims to determine the differences in learning outcomes between students which follows the course of study with students who do not join the course in terms of. Lessons English lessons are considered difficult by most students. This is caused by many factors diantanya class hours less, the lack of professionalism of teachers, learning styles unpleasant and so forth. To that end, so that more students master the learning should be given an extra hour, one of them with learning course program. The course is a proactive and systematic efforts in facilitating individuals achieve optimal levels of development, the deve opment of effective behavioral, environmental, and an increase in function or benefit of individuals in their environment. The population in this study is the whole class at SMPN 19 MONCONGLOE. sample includes 20 Siwa took courses and 20 students who did not join the course. In the data collection writers do the following things, namely observation, documentation, and giving the test tothe two groups. The results showed that there were differences in learning outcomes in literacy significant with an average of 90% for students who take courses to learn and 80% for students who do not follow the course to determine whether there are differences in the ability to read the learning outcomes of the two groups, the researchers used data analysis is test test, this is because the data obtained from this research is the normal data differences in learning outcomes of reading skills among students who take courses to learn with students who are not taking a course.